MANAJEMEN PEMBIAYAAN PENINGKATAN KOMPETENSI GURU PEMBIMBING KHUSUS JENJANG PENDIDIKAN DASAR - Nihan Kristiyani; Warman; Widyatmike Gede Mulawarman; Muhlis; Anggra Prima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to find out and analyze the financing management of Competency Improvement Activities for Special Supervisors at the Basic Education Level The research method applied in this study is a qualitative descriptive research method with a case study approach located in UPTD. Samarinda City Center for Disability Services and Inclusion Education. This activity is the implementation of one of the tasks of this institution in assisting inclusion schools in improving the competence of Special Supervisors. Financing management that is carried out includes planning, implementation and evaluation of financing. The results obtained from this study are that the Special Supervisor Teacher Competency Improvement Activity can be carried out using a cost of Rp. 80,579,000 (Eighty Million Five Hundred Seventy Nine Thousand Rupiah), with a total of 366 Special Supervisor Teachers, for 5 (five) days, consisting of Basic Training and Advanced Training.